Strengthening Digital-Based Education to Prevent Sexual Violence Against Students through Higher Education - Hasruddin Nur; Suardi; Hasanudin Kasim; Besse Wulandari Aziz (Universitas Pendidikan Ganesha, 2025)
Sexual violence persists as a significant and pervasive challenge within higher education, necessitating urgent, systemic, and evidence-based interventions. This study evaluates the effectiveness of digital- based education for the prevention and management of sexual violence in Indonesian universities. Employing a mixed-methods approach, the research integrates quantitative surveys from 735 respondents, Partial Least Squares Structural Equation Modeling (PLS-SEM), and qualitative thematic analysis of stakeholder interviews to examine institutional performance across three key dimensions: policy dissemination, value promotion, and training. The findings demonstrate that digital policy dissemination exerts a significant influence on perceived institutional effectiveness, while value promotion and training, although positively received, do not show statistical significance in shaping these perceptions. Thematic analysis underscores the critical roles of inclusive communication, accountable leadership, contextually relevant training, and victim-centered response mechanisms. The study concludes that digital education can be transformative when implemented through participatory, culturally sensitive, and structurally embedded practices. The novelty of this research lies in its empirical validation of a digital preventive framework adapted to the socio-cultural realities of Indonesian higher education, thereby contributing unique insights from the Global South to global discourses on campus safety and offering guidance for the development of equity-driven, survivor- responsive digital interventions within academic institutions.